Vascular Endothelial Growth Factor Expression in the Retinal Pigment Epithelium Is Essential for Choriocapillaris Development and Visual Function - Marneros, Alexander G. (American Society for Investigative Pathology, 2005)
The choroid in the eye provides vascular support for the retinal pigment epithelium (RPE) and the photoreceptors. Vascular endothelial growth factor (VEGF) derived from the RPE has been implicated in the physiological regulation of the choroidal vasculature, and overexpression of VEGF in this epithelium has been considered an important factor in the pathogenesis of choroidal neovascularization in age-related macular degeneration. Here, we demonstrate that RPE-derived VEGF is essential for choriocapillaris development. Conditional inactivation of VEGF expression in the RPE (in VEGF(rpe)(−/−) mice) results in the absence of choriocapillaris, occurrence of microphthalmia, and the loss of visual function. Severe abnormalities of RPE cells are already observed when VEGF expression in the RPE is only reduced (in VEGF(rpe)(+/−) mice), despite the formation of choroidal vessels at these VEGF levels. Finally, using Hif1a(rpe)(−/−) mice we demonstrate that these roles of VEGF are not dependent on hypoxia-inducible factor-1α-mediated transcriptional regulation of VEGF expression in the RPE. Thus, hypoxia-inducible factor-1α-independent expression of VEGF is essential for choroid development.